Enhanced photocatalytic efficiency of NiS/TiO2 composite catalysts using sunset yellow, an azo dye under day light illumination. (January 2015) - Rajamanickam, D.; Dhatshanamurthi, P.; Shanthi, M.
Graphical abstract: Highlights: NiS/TiO2 was successfully synthesized by sol–gel method. This new method of preparation gives a homogeneous dispersion of NiS on TiO2 . Degradation activity of NiS/TiO2 is found to be more efficient than other catalysts. Addition of oxidants enhances the degradation efficiency significantly. COD measurements reveal the complete mineralization of dye molecules. The catalyst is found to be reusable. Abstract: To improve the solar light induced photocatalytic application performances of TiO2, in this study, the NiS modified TiO2 composite photocatalysts with various ratios of NiS to TiO2 were prepared by sol–gel method. The catalyst was characterized by X-ray diffraction (XRD), high resolution scanning electron microscope (HR-SEM), high resolution transmission electron microscope (HR-TEM), energy dispersive spectra (EDS), diffuse reflectance spectra (DRS), photoluminescence spectra (PL), X-ray photoelectron spectroscopy (XPS), and Brunauer–Emmett–Teller (B–E–T) surface area measurement methods. The photocatalytic activity of NiS/TiO2 was investigated for the degradation of sunset yellow (SY) in aqueous solution using solar light. The NiS/TiO2 is found to be more efficient than prepared TiO2 and TiO2 –P25 at pH 7 for the mineralization of SY. The effects of operational parameters such as the amount of photocatalyst, dye concentration and initial pH on photo mineralization of SY have been analyzed. The degradation was strongly enhanced in the presence of oxidants such as H3 K5 O18 S4 (Oxone), KIO4, and KBrO3 . The mineralization of SY has been identified by COD measurements. The catalyst is found to be reusable.